How crosscutting weak ties are established—the case of Muslims in Europe. Issue 2 (26th January 2016) - Damstra, Alyt; Tillie, Jean
ABSTRACT: Building on the work of Granovetter [1973. "The Strength of Weak Ties." American Journal of Sociology 78 (6): 1360–1380.], weak ties are assumed to play a vital role in processes of integration. In this paper, the focus lies on weak ties that cut across ethnic boundaries, connecting Muslim immigrants to members of the ethnic majority in six European host societies. The aim is twofold: a descriptive analysis of the existence of those crosscutting weak ties amongst different groups of Muslim immigrants and an explanatory analysis focusing on the structural factors that make the establishment of such ties more likely. In the latter part, the native populations are also taken into account, allowing for a bidirectional perspective. Using ordinal logistic regression models, we found that emancipatory factors such as education and language skills are positively associated with having weak ties, whereas conservative values and religiosity decrease the likelihood of establishing many weak ties. A diverse neighbourhood appears to play a pivotal role in the formation of weak ties from both a native and an immigrant perspective.